Simulação computacional do LiBPO4 (B = Ba, Sr e Ca) e a influência dos mecanismos de defeitos gerados sobre os processos de dopagem-redução de íons terras-raras - Santos, Ricardo Daniel Soares (2019)
Phosphorus materials formed from orthophosphates have been widely used in various technological applications such as new inoganic matrices of special interest, such as in the medical field can be used as bio-sensors devices, already in the industrial area, is employed in developing studies as luminescent devices. Among the various phosphors, the family of lithium orthophosphates LiBPO4 (B = Ba, Sr and Ca) presents a hexagonal structure with different spatial groups, appearing as matrices of materials, which when doped by rare earth ions (RE) have interesting properties of defects. In order to study the incorporation of the divalent (RE2+) and trivalent (RE3+) dopants we used the atomistic computational simulation method. In the first part, new short-range potentials were obtained that reproduced the network parameterization, like all precursor oxides and dopant oxides. In the sequence, the relationship between the binding lengths of the RE3+-O2- interactions for the simulated parameters in relation to the experimental ones for the whole family was studied. In the second part, extrinsic defects were studied for the incorporation of the divalent (RE2+=Eu2+) and trivalent (RE3+=D3+, D3+, Tb3+, Gd3+, Eu3+, Eu3+, Sm3+, Nd3+, Pr3+, Ce3+ and La3+) dopant ions at all sites of compound. From the results obtained it was shown that all dopants tend to be incorporated in the sites of divalent cations (B2+ = Ba, Sr and Ca) than in lithium (Li+) and phosphorous (P5+) sites and the defects by lithium vacancies and anti-site defects are both probable. It was also verified for LiCaPO4 through the sum of the binding valency that the tendency in the variation of the binding lengths and the valence states between the RE3+ -O2- ions when incorporated in the Ca2+ sites presented values for the valence states in data available in the literature. Finally, it was studied the doping process - reduction of the valence of the Eu (Eu3+->Eu2+) ions applied under different conditions: open atmospheres and with reducing agents H2(g) and CO(g) by different defect mechanisms. It was observed that the reducing agent H2(g) was energetically more favorable and that the mechanisms of defects involving the open atmosphere and the reducing agent CO(g) were not efficient.